Clinical Practice Guidelines for diagnosis and treatment of Duchenne muscular dystrophy. Peruvian Neurology Society. Short Version - Martínez-Esteban, Peggy (2022)
Objective: to provide evidence-based clinical recommendations for the diagnosis and treatment of Duchenne Muscular Dystrophy. Methods: a guideline development group (GEG) was formed that included specialized physicians in the fields of neurology, neuropediatrics, genetics, and methodology. The GEG asked eight clinical questions to be answered by recommendations in this clinical practice guidelines (CPG). We conducted a systematic search and - when deemed relevant - primary studies in Medline, Scopus, and the Cochrane Controlled Register of Trials during 2021 were reviewed. Evidence was selected to answer each of the clinical questions posed. Certainty of the evidence was assessed using the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) system. In periodic work meetings, the GEG used the GRADE methodology to review the evidence and formulate recommendations, points of good clinical practice, and a diagnosis and treatment flowchart. Results: this CPG addressed eight clinical questions, divided into three topics: screening, diagnosis, and treatment. Based on these questions, fifteen recommendations were formulated (10 strong, 5 conditional) and 11 points for good clinical practice. Conclusion: this paper summarizes the methodology and evidence-based conclusions of the CPG for the diagnosis and treatment of Duchenne muscular dystrophy.